STUDY ON MORPHOLOGICAL CHARACTERS OF INDONESIAN LITTER FROG (LEPTOBRACHIUM, MEGOPHRYIDAE) - Muhammad Fakhri Fauzan; Achmad Farajallah; Amir Hamidy (Treubia, 2023)
Leptobrachium from Southeast Asian populations previously were recognized as a single speciesLeptobrachium hasseltii Tschudi. Taxonomic reassessment revealed that Leptobrachium consists of somecryptic species due to similarities in their morphological appearance but diverse in molecular characters.Among the Indonesian populations, Leptobrachium was split into seven species (L. hasseltii, L. nigrops,L. waysepuntiense, L. hendricksoni, L. ingeri, L. abbotti, and L. montanum). Specifically, L. hasseltii isseparated into two groups; the Sumatran-Javan and the Bali populations. In this study, we analyzed themorphological data of 100 individuals of Leptobrachium to evaluate their morphological differences.The morphological differences expressed by analysis of variance (ANOVA) and principal componentanalysis (PCA) revealed significant differences between each Leptobrachium and four morphologicalcharacters suitable for species identification (the iris color, color pattern, humeral and femoral gland).The morphological differences also showed that the Bali population probably is undescribed species.